Answer:
Part A:
[tex]v_y=-63 m/s[/tex]
Part B:
[tex]v_y=-24.67792 m/s[/tex]
Explanation:
Part A:
The formula we are going to use is:
[tex]v_{y}= \frac{dy(t)}{dt} \\v_y=\frac{d(b-ct+dt^2)}{dt} \\v_y=-c+2d*t[/tex]
For finding the initial velocity we put t=0 in above formula:
[tex]v_y=-c+2d*t[/tex]
[tex]v_y=-c+2d*0[/tex]
[tex]v_y=-c[/tex]
c=63 So,
[tex]v_y=-63 m/s[/tex]
Part B:
When lander reaches the lunar surface y(t)=0
[tex]y(t)=b-ct+dt^2=0[/tex]
Using Quadratic formula:
[tex]t=\frac{-b\±\sqrt{b^2-4ac} }{2a}[/tex]
In our case:
[tex]t=\frac{c\±\sqrt{c^2-4db} }{2d}[/tex]
[tex]t=\frac{63\±\sqrt{(63)^2-4*1.05*800} }{2*1.05}[/tex]
[tex]t=41.75139sec[/tex] [tex]t=18.248606sec[/tex]
We are going to choose t=18.248606 sec because it is smaller.
[tex]v_y=-c+2d*t[/tex] (Calculated above)
[tex]v_y=-63+2(1.05)*18.248606[/tex]
[tex]v_y=-24.67792 m/s[/tex]